High-resolution analysis of chromosome conformation in hyperthermophilic archaea - Naomichi Takemata; Stephen D. Bell (STAR Protocols, 2021)
Summary: Chromosome conformation capture (3C) techniques are emerging as promising approaches to study genome organization in Archaea, the least understood domain of life in terms of chromosome biology. Here, we describe a 3C technique combined with deep sequencing for the hyperthermophilic archaeal genus Sulfolobus. Instead of using restriction enzymes compatible with fill-in labeling, this protocol uses the 4-bp blunt cutter AluI to generate high-resolution (up to 2 kb) contact maps from Sulfolobus species.For complete details on the use and execution of this protocol, please refer to Takemata and Bell (2021).